Sewage Sludge Incineration: Gas Emissions and Heavy Metals Studies - Nashbat, Mohammed I. A. (1999)
The overall objective of this study was to develop and innovate sludge treatment technology especially related to sewage sludge combustion. And to investigate the thermal destruction of sewage sludge. Sewage sludge characteristics were studied. Sewage s1udge is composed of organic containing macro-nutrients such as nitrogen (N) and phosphor (P) and a number of trace of heavy metals as e.g. zinc (Zn). However, sewage sludge also contains components that are considered to be harmful to the environment. Moisture content was found to be 70%, specific gravity was equal to 1.107, and finally ash content was equal to 50%. The temperature effect at the different gas emissions during sewage sludge incineration using electrical muffle furnace was studied. It was found that increasing the temperature would increase both sulphur and nitrogen oxides (NO, N02),whereas it would decrease carbon oxides (CO. C02). The optimum temperature for sewage sludge incineration with minimum air pollution was found to be 900 dc. A study of the effect of limestone addition at the different gas emissions during sewage sludge incineration was performed. It was found that adding limestone during sewage sludge incineration win slightly increase nitrogen oxides by 5-10% and carbon oxides by 0.02-11% while it effectively decrease sulphur dioxide emissions by 65% at 900°C. The optimum reduction in sulphur dioxide emissions can be achieved by using 2.0 CaiS mole ratio.